Carbonate blocks found in muddy sediment off Cape Breton Island, Nova Scotia:: pieces of small authigenic carbonate mounds and vents related to hydrocarbon seeps? - Wallace, Peter; Harrington, Matt; Cook, Ryan (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2006)
ABSTRACT Carbonate blocks brought up from the seaﬂoor during drag ﬁshing in a small restricted area offshore northern Cape Breton Island are irregularly shaped and range in size from 6 cm3 to >1 m3. They have smooth to "clinkery", dendritic, or "popcorn-surface" structures, can be layered to massive, and are porous. Many are highly porous and/or eroded. They contain ﬁne-grained siliciclastic material (mud to granule sized) with minor amounts of bioclasts cemented by calcite. Three blocks have vent structures and some have pores lined by ﬁne-grained sparite. Seismic lines in the vicinity of the discovery area show acoustic turbidity, bright spots interpreted to be hydrocarbon seeps, diaper-like structures, and columnar sediment disturbances that reach to bedrock. Outside the immediate area, pock marks occur on the sediment surface. Carbon isotope values from shelly material cemented in the blocks range from δ13C = -9.41 to -35.27 ‰ PDB (Pee Dee Belemnite) with an algae encrustation or bacterial mat yielding -61.38 ‰ PDB. From the isotopic analysis and the seismic interpretation we are conﬁdent that these blocks are pieces of carbonate mounds and vents formed by methanogenesis of hydrocarbon from slow seeps on the seaﬂoor, the hydrocarbon originating either within the recent sediment and/or from bedrock, most likely the latter. The ecology of these mounds has not been studied and needs further work in this area of active commercial ﬁshing.